Kubo Kalinaw - Canimo, Angel Marc, Damian, Jzeaska Mariella, Echevarria, Aira Shayne, Montoya, Mary Grace, Siva, Ivy Joy, Reyes, Gracell. 4 0 16; 5 (2024)
DEFINITION OF THE PROJECT The proposed project is a two-story private resort inspired by the modern bahay kubo, incorporating elements of Philippine architecture. Outdoor amenities include an adult and kiddie pool, a mini jacuzzi, a bonfire area, an open-air movie area, an outdoor bathroom, and parking for two to three cars. The ground floor features a living room, a combined dining and kitchen area, a bedroom, and a bathroom. The second floor includes two additional bedrooms with a balcony, an entertainment room, a bathroom, and a relaxing area with an open hammock for lounging. NAME OF THE PROJECT The proposed private resort is called Kubo Kalinaw to reflect its goal of offering a quick escape and relaxation in the busy city of Metro Manila. The resort is designed with a modern bahay kubo theme, blending the charm of the traditional Filipino house with a peaceful, provincial ambiance. The bahay kubo, an iconic symbol of Filipino culture, represents simplicity and close connection to nature. At the resort, we've incorporated this design by using traditional materials like nipa, rattan, bamboo and other native materials that have relation to the theme, to stay true to its roots. The word Kubo means nipa hut, while Kalinaw is a Cebuano word that translates to serenity or tranquility. Together, Kubo Kalinaw captures the essence of the resort, a place where guests can experience calm and relaxation in the midst of the fast-paced city life, while also enjoying a touch of Filipino culture. The resort aims to provide a hassle- free getaway, offering a peaceful retreat where visitors can unwind and feel connected to the country's traditions.
Feasibility Study: (Bachelor of Science in Real Estate Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2